Web-based interface to collect data on dairy cattle performance from medium and large-scale farmers in Kenya, Tanzania and Ethiopia - CGIAR Research Program on Livestock (2021)
A web-based interface has been developed and linked to the African Dairy Genetics Gain (ADGG) platform as a self-service portal for data from medium and large scale farms registered either directly or through farmer organizations on the platform.